Strain design method of buried pipeline crossing fault. (November 2019) - Liu, Wu; Guo, Qin; Qiao, Chunfeng; Hou, Wanggang
Abstract: Faults are ground ruptures and disoperations that occur in crustal rock strata. Long distance buried pipeline crossing a fault zone is prone to axial fracture, lateral dislocation or buckling failure, which can cause the leakage of the pipeline medium or secondary disasters. Therefore, we established a finite element model of buried pipelines crossing a strike-slip fault, taking active faults and pipelines as the research objects, and considering the material nonlinearity of pipeline and fault soil, the nonlinear geometric deformation of the pipeline and the contact nonlinearity between pipes. The mechanical response behavior of buried pipelines under fault displacement loads was analyzed, and the influence of pipeline size and material, fault site soil conditions and pipeline operation conditions on pipeline mechanical properties was studied. According to the influential law of parameters, dimensionless factors such as pipe material, the cohesive force of soil and internal pressure of the pipeline were adopted. Multiple linear and nonlinear regression theories were utilized to fit the simplified formula for strain calculation of buried pipeline crossing a strike-slip fault. Our model is available for reference in the design and safety assessment of the buried pipeline crossing the strike-slip fault. Highlights: The finite element model of  pipeline buried under the action of a strike-slip fault is established; Buried pipeline under fault-displacement load mechanical response behavior and the mechanical properties are analyzed; A simplified calculation formula for the strain of buried pipeline crossing a strike-slip fault is established.